Multitasking, Pelatihan dan Kecepatan Pengambilan Keputusan Bisnis - Anton Sunardi (MANAZHIM, 2022)
In an organization or company the management has a big role in the performance of its employees. Training in the form of motivation has an influence on the speed of decision-making that is strategic or business in nature. Previous research believes that a good educational background, skills, and cognitive abilities are the main factors causing the most dominating success in decision making. In the current era, the level of stress and work pressure is getting higher because mostly all professionals are required to be able to achieve the main goal of the company's business strategy, namely speed in making decisions. This study aims to describe, analyze and explore how the effects of multitasking on employees business decision making. The research data collection involved 3 respondents. Data were collected through interviews and observations. Researchers go directly to the field to get accurate and in-depth data through various relevant sources. This study found that in addition to proper training and motivation, there are other things that cause the decision process to be hampered, namely pressure factors, differences in perceptions, and excessive stress levels resulting in job fragmentation.